Analisis Frasa Nominal Subordinatif pada Teks Berita Suara.Com “Tak Semuanya Sehat, Sayuran Jenis Ini Justru Picu Tekanan Darah Tinggi” - Risma Tiyasti Ningrum; Asep Purwo Yudi Utomo (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
Subordinate nominal phrases are a collection or consist of two or more words whose two elements are not equal. Some have a position as the superior element or core of the phrase, and who have a position as subordinate elements or are referred to as additional explanatory phrases. This article aims to find out the subordinative nominal phrase contained in the Suara.com news text entitled "Not All Healthy, Vegetables of This Type Precisely Trigger High Blood Pressure" edition of September 24, 2020, according to the composition. The method used in writing this article is qualitative data analysis method by searching, finding and classifying each subordinative nominal phrasing contained in the Suara.com news text entitled "Not All Healthy, Vegetables of This Type Precisely Trigger High Blood Pressure" edition of September 24, 2020. The result obtained from this research is the discovery of subordinate nominal phrases in accordance with their respective arrangements. With this research is expected to help the community, especially students to be able to understand and be able to make subordinative nominal phrases in news text sentences or not in the learning of Indonesian language and the world of literacy.